(untitled) (International Journal of Engineering and Computer Science, 2016)
Serverless computing has become an innovative model within computing clouds, which has become a revolutionary model for developing applications. Thanks to serverless architecture exclusion of infrastructure management aspects, the developers can concentrate only on the application code improvements. In this paper, the important criteria related to serverless computing will be discussed, with focus on the performance comparison, scalability, and cost issues. The discussion starts with the performance characteristics of the serverless business model from the perspective of business value and discusses limits such as cold-start latency and resource scarcity which makes it difficult for serverless to address high-concurrency workloads. It goes further in explaining details of scalability whereby; serverless architecture is more efficient in handling dynamic workload through automatic scaling and it addresses issues of bottlenecks in dependent systems. Efficiency is evaluated based on an analysis of the comparison of all the pay-per-use models against the traditional and cloud infrastructure and the situations that may make serverless computing cheap or expensive. Also, the paper explores various issues associated with serverless, including vendor lock-in, debugging, and security issues while giving guidelines and choice of design patterns for optimum and effective serverless environments. The final part of the study analyzes the actors, drivers, and opportunities, as well as the future growth and trends of serverless computing, proposing it as the underlying technology for innovative applications in the IoT, artificial intelligence, and data analytics fields. This evaluation is useful to organisations and developers so as to realise the advantages of using the serverless architecture and at the same time avoid its disadvantages.